A cross sectional study on food safety knowledge among adult consumers. (May 2019) - Ruby, Genevie Eleanor; Ungku Zainal Abidin, Ungku Fatimah; Lihan, Samuel; Jambari, Nuzul Noorahya; Radu, Son
Abstract: The purpose of this study was to assess the consumers' food safety knowledge and its determinants. The analysis was based on data collected through a cross-sectional survey in East Malaysia, which described the knowledge about personal hygiene, foodborne disease symptoms, high-risk foods, cross-contamination, and temperature control held by Sibu-based consumers. Up to 99.5% of consumers correctly answered the question on hand hygiene in food handling. However, only 23.3% had a detailed knowledge of the temperature effect on bacterial growth in food. The level of food safety knowledge differed by gender, age, education level, number of children and food preparation frequency. The logistic regression model used for this data found a high level of food safety knowledge among tertiary graduates (OR = 42.26; 95% CI: 9.97, 179.06). It also highlighted the importance of food safety knowledge as an effort to control foodborne diseases (FBD), by focusing on consumer food handling in the home and how to extent the benefits of food safety education to the whole society. Highlights: Food safety knowledge among adult consumers, on the whole, was considered good. The respondents had very poor knowledge in temperature control. The knowledge level not impacted by employment status and number of family members. The predictors for knowledge level were tertiary graduates and the female gender.